Agricultural waste as growing media component for the growth and flowering of Gerbera jamesonii cv. hybrid mix - Atif Riaz; Adnan Younis; Imran Ghani; Usman Tariq; Muhammad Ahsan (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study was performed to investigate the impact of various agricultural wastes as potting media on growth, yield, and quality flower production of Gerbera jamesonii L. cv. hybrid mix, and to estimate hazardous impact of chemical fertilizers. Method The effect of four agricultural substrates viz. farm yard manure, coconut coir dust, Lahore compost (local produce), and leaf compost combined with conventional media i.e., garden soil, sand, and silt in equal proportion was studied for commercial production of gerbera. All the treatment combinations were arranged into completely randomized design with three replicates. Result Visible variations in morphological characters were evidenced among conventional medium and agricultural waste as substrates with significant superiority of flower quality and plant growth. The presented results showed that treatment combination of silt, coconut coir dust, and top soil (SCT) produced maximum plant height while mixture of silt, Lahore compost and top soil (SLT) gave maximum number of leaves per plant and maximum flower stalk thickness. The highest values for leaf area, number of roots, flower fresh to dry weight ratio and number of flowers per plant were achieved in combination of silt, farm yard manure, and top soil (SFT) whereas silt, sand, and top soil (SST) presented maximum flower diameter, maximum fresh, and dry weight of flowers. Chemical characteristics of growing media showed superiority of silt, farm yard manure, and top soil (SFT) and silt, sand, and top soil (STL) for available phosphorus and potassium with values of 27.0 and 500 ppm, respectively. Conclusion It was concluded that the application of waste materials in combination with silt provided positive results for vegetative and reproductive growth of Gerbera jamesonii plants.